Starbreaker - Bouchet, Amanda (Bouchet, Amanda. Nightchaser, 2020)
Captain Tess Bailey and Shade Ganavan are the galaxy's Most Wanted, while the universe is on the brink of catastrophic war. As their attraction builds, they must decide if they trust each other to change the course of history together.